Interaction between mDia1 and ROCK in Rho‐induced migration and adhesion of human dental pulp cells. (23rd December 2015) - Cheng, L.; Xu, J.; Qian, Y. Y.; Pan, H. Y.; Yang, H.; Shao, M. Y.; Cheng, R.; Hu, T.
Abstract: Aim: To investigate the effects of mammalian homologue of Drosophila diaphanous‐1(mDia1) and Rho‐associated coiled‐coil‐containing protein kinase (ROCK) on the migration and adhesion of dental pulp cells (DPCs). Methodology: Lysophosphatidic acid (LPA) was used to activate Rho signalling. mDia1 and ROCK were inhibited by short interfering RNA and the specific inhibitor, Y‐27632, respectively. The migration of DPCs was assessed using the transwell migration assay and scratch test. Formation of cytoskeleton and focal adhesions(FAs) was observed by confocal laser scanning microscopy. Cell adhesion and spreading assays were performed. Phosphorylation of focal adhesion kinase (FAK) and paxillin was detected by Western blotting, and the bands were analysed using Adobe Photoshop CS5 software. All experiments were performed at least three times, and data were analysed with one‐wayanova and a post hoc test. Results: LPA‐triggered activation of Rho and inhibition of ROCK significantly increased the cell migration rate. Cell migration was inhibited by silencing mDia1. mDia1 silencing and ROCK inhibition suppressed the LPA‐induced formation of the cytoskeleton, FA and phosphorylation of FAK and paxillin. Inhibition of ROCK or mDia1 facilitated early cell adhesion and spreading; by contrast, the combined inhibition of ROCK and mDia1 neutralized these effects. Conclusions: mDia1 promoted RhoA‐induced migration of DPCs, but ROCK had an opposite effect. Both mDia1 and ROCK participated in cytoskeleton formation and adhesion of DPCs. The interactions between mDia1 and ROCK might influence dental pulp repair by determining the migration and adhesion of DPCs.